Analysis of Personal Hygiene, Premises Sanitation and Equipment Sanitation on Coliform Bacteria Content in Bubble Drinks - Nur Khalifah Nur; Yulia; Susilawati (Jurnal teknologi Kesehatan Borneo, 2023)
Abstract. Ice bubble (bubble drink) is a popular ready-to-eat drink and is in great demand by the public because of the variety of flavors with a mixture of bubble topping (boba) in it. The personal hygiene of drink handlers, the cleanliness of sales locations, and the equipment used can all cause microbiological damage to bubble ice, which can lead to coliform bacteria contamination of bubble ice drinks. Coliform bacteria can cause various diseases, one of which is diarrhea. This study aims to determine the relationship between personal hygiene, place sanitation, and equipment sanitation and the content of coliform bacteria in bubble ice drinks in Pontianak City in 2022. According to the findings, coliform bacteria were present in 27 out of the 30 samples that had undergone coliform bacteria testing. This study obtained results of poor personal hygiene for as many as 26 people (86.7%), poor sanitation of selling places for as many as 27 people (90%), and poor sanitation of equipment for as many as 27 people (90%). This study also shows that there is a relationship between personal hygiene and coliform bacteria content with a value of p = 0.039, a relationship between place sanitation and coliform bacteria content with a p value = 0.02, and a relationship between equipment sanitation and coliform bacteria content in ice bubble drinks. with a p value of 0.039. Therefore, it is necessary to pay attention to the cleanliness of tools, the environment, and individual traders so that bubble ice is safe for consumption